Questioning the ornament through a morphological approach to the visible (Itinera, 2021)
The paper investigates the question of the ornament starting from a parallelism between biological- architectural ornaments and decorative-artistic ones. The element of innovation and the emergency of the ornament allow to consider images as if they were living organisms and to highlight their becoming through new forms. Starting from a morphological point of view, from Johann Wolfgang von Goethe to the contemporary morphology, the ornament is strictly connected to the dynamics of forms and to a particular approach to the visible. The ornamental dynamics, according to the binomial form-function, open the dimension of the visible to new perspectives and foreshadow potentially infinite changes. The essay analyzes the consequences in the production of visible forms and in the attribution of meanings, but also the political function of images, with particular reference to the idea of an economy of visible forms.
Keywords: Ornament, morphology, images, economy of visible forms.